Site selection of ocean current power generation from drifter measurements. (August 2015) - Chang, Yu-Chia; Chu, Peter C.; Tseng, Ruo-Shan
Abstract: Site selection of ocean current power generation is usually based on numerical ocean calculation models. In this study however, the selection near the coast of East Asia is optimally from the Surface Velocity Program (SVP) data using the bin average method. Japan, Vietnam, Taiwan, and Philippines have suitable sites for the development of ocean current power generation. In these regions, the average current speeds reach 1.4, 1.2, 1.1, and 1.0 m s −1, respectively. Vietnam has a better bottom topography to develop the current power generation. Taiwan and Philippines also have good conditions to build plants for generating ocean current power. Combined with the four factors of site selection (near coast, shallow seabed, stable flow velocity, and high flow speed), the waters near Vietnam is most suitable for the development of current power generation. Twelve suitable sites, located near coastlines of Vietnam, Japan, Taiwan, and Philippines, are identified for ocean current power generation. After the Kuroshio power plant being successfully operated in Taiwan, more current power plants can be built in these waters. Highlights: Site selection of ocean current power generation is optimally from drifter data. Vietnam, Japan, Taiwan, and Philippines have suitable sites. In these regions, the average current speeds reach 1.0–1.4 m s −1 . An index I related to the site selecting of current power generation is designed. The charts of current speeds and 12 suitable sites in the East Asia are provided.